Temporal corridors of forces and moments, and injuries to pelvis-lumbar spine in vertical impact simulating underbody blast. (March 2023) - Yoganandan, Narayan; Humm, John; Baisden, Jamie; Moore, Jason; Pintar, Frank; Wassick, Michael; Barnes, David; Loftis, Kathryn
Abstract: Pelvis and lumbar spine fractures occur in falls, motor vehicle crashes, and military combat events. They are attributed to vertical impact from the pelvis to the spine. Although whole-body cadavers were exposed to this vector and injuries were reported, spinal loads were not determined. While previous studies determined injury metrics such as peak forces using isolated pelvis or spine models, they were not conducted using the combined pelvis-spine columns, thereby not accounting for the interaction between the two body regions. Earlier studies did not develop response corridors. The study objectives were to develop temporal corridors of loads at the pelvis and spine and assess clinical fracture patterns using a human cadaver model. Vertical impact loads were delivered at the pelvic end to twelve unembalmed intact pelvis-spine complexes, and pelvis forces and spinal loads (axial, shear and resultant and bending moments) were obtained. Injuries were classified using clinical assessments from post-test computed tomography scans. Spinal injuries were stable in eight and unstable in four specimens. Pelvis injuries included ring fractures in six and unilateral pelvis in three, sacrum fractures in ten, and two specimens did not sustain any injuries to the pelvis or sacrum complex. Data were grouped based on time to peak velocity, and ± one standard deviation corridors about the mean of the biomechanical metrics were developed. Time-history corridors of loads at the pelvis and spine, hitherto not reported in any study, are valuable to assess the biofidelity of anthropomorphic test devices and assist validating finite element models.